Peran Media Sosial Facebook dalam Mempromosikan Makanan Lokal Jagung Titi di Desa Laranwutun Kabupaten Lembata - Ronaldo T. G. Panggo; Mikhael Rajamuda Bataona; Urbanus Ola (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
Information technology plays a crucial role in supporting the growth of the digital economy, including in the micro and traditional business sectors. One example is the use of digital technology to increase sales of titi corn in Laranwutun Village, Lembata Regency. Titi corn is a traditional food from East Nusa Tenggara, particularly in the eastern Flores region of Solor, Adonara, and Lembata. However, this specialty food is not yet widely known due to minimal promotion and marketing, particularly on social media. This has resulted in limited market share and low incomes for local communities. This study used qualitative methods through direct interviews with titi corn entrepreneurs. The research process was divided into three stages: planning, preparation, and implementation. The theory used refers to the concept of digital marketing, specifically the use of Facebook as a promotional tool. This study examines the extent to which Facebook can increase marketing reach, expand the market, and facilitate the promotion of titi corn. The results show that Facebook plays a significant role in promoting and increasing titi corn sales. This social media platform facilitates the delivery of product information, reaches a wider consumer base, and builds brand awareness. Furthermore, Facebook enables direct interaction between producers and consumers, thereby increasing customer trust and loyalty to local products. This digital promotion strategy also opens up opportunities for collaboration with traditional culinary communities and local MSMEs, which can strengthen marketing networks. These findings emphasize the importance of preserving local food through an integrated digital approach. By optimizing social media, titi corn will not only gain wider recognition but also have the potential to become a superior regional product that supports sustainable and inclusive community economic empowerment.